Consistency in personality trait judgments across online chatting and offline conversation - Wu, Wenjie; Mitchell, Peter; Lv, Yingguo (Frontiers in Psychology, 2023)
Past research has suggested that people utilize various nonverbal cues to make personality judgments in either real-world or online environments, but little is known about the extent to which a person would be perceived consistently across realistic and virtual contexts. The present study was to investigate this issue, exploring the extent to which the same target was judged consistently in terms of empathic and big-five traits across online text-based chatting and offline conversation, and to pinpoint how the judgments occurred in the two contexts. In the formal procedure, 174 participants were asked to make trait judgments and evaluated the observable cues about the partner after chatting online and after watching the partner (who the participant did not know was the same person in the online chatting) in a real-world conversation. Results demonstrated: (1) participant made consistent judgments of each trait about the same target across the online chatting and the offline conversation; (2) many cues in each context were employed to drive trait judgments whereas few cues validly revealed the self-reported assessments of the traits. The results were discussed based on the empirical and theoretical work in person perception.